Unhealthy by design: health & safety consequences of the criminalization of homelessness. Issue 2 (3rd July 2021) - Westbrook, Marisa; Robinson, Tony
ABSTRACT: Although U.S. cities are expanding "anti-homeless" legislation – such as laws against public sleeping or use of shelter – there is little research on the public health consequences. Officials argue that laws forbidding public sleeping, and other forms of behavioral supervision, are "tough love" strategies to compel people experiencing homelessness to improve their health by leaving the streets and using services. To test these claims and understand the public health implications of "quality of life" laws enforced against the homeless, this paper reports on a community-based participatory research survey of 484 individuals experiencing homelessness in Denver, Colorado. Results indicate that respondents have worse sleep habits and mental health outcomes when worried about police contact; people seek isolated sleeping locations to avoid police contact, resulting in more assault; and individuals are more at risk of exposure to weather-related hazards if they have been instructed to quit using shelter. This evidence contradicts the "tough love" defense of the criminalization of homelessness, as the health and wellbeing of people experiencing homelessness is worsened through "quality of life" policing. Results from this survey have been used by community partners and local policymakers to successfully advance district court arguments that anti-homeless legislation in Denver, Colorado is unconstitutional.